Emprego da micorremediação para a redução da toxicidade de lixiviado proveniente de aterro sanitário - Pesenti, Maria Eduarda Aranega (2023)
One of the major difficulties in solid waste management is the treatment of leachate generated in waste degradation. Due to its complex composition, the physical-chemical and biological treatments that are currently used to treat this effluent are not as efficient in removing toxicity. A new technology that has been studied for the treatment of toxic compounds is mycoremediation, a technique that uses fungi to degrade the compounds resulting in the partial or total removal of pollutants. Toxicity tests with Allium cepa have been used to verify the toxicity levels of effluents. In this context, this work aimed to employ the mycoremediation process in leachate from landfills to minimize the toxic effects of the effluent. In this study, 3 autochthonous fungi from soil and landfill leachate samples were selected for mycoremediation (L.B.1 - 1, L.B.2 - 1, S.1.1 - 5), similar to Candida spp., Trichophyton spp. and Mucor spp., respectively. Experimental units were set up with different concentrations of leachate (0, 10, 25, 50 and 100%) that were inoculated with the selected fungi and incubated for 7 days. The fungus L.B.2 - 1 underwent two incubation periods, 7 (L.B.2 - 1) and 9 days (L.B.2 - 1.D), respectively. After the incubation, the cell mass and the liquid extract of the experimental units were separated. Toxicity tests (bioassays) were performed with the filtered extracts from the experimental units, using 2 mL to inoculate the seeds in Petri dishes. After the incubation time, macroscopic analyzes were carried out (count of germinations and measurement of root growth), with the purpose of performing the calculations of the macroscopic analysis indices. From the analysis of the results, it was found that both samples have good diversity of fungi. After the mycoremediation process, fungi L.B.1 - 1 and L.B.2 - 1.D showed cell mass in all leachate concentrations, indicating greater adaptation of the organism, while for experimental units L.B.2 - 1 and S.1.1 - 5 there was the absence of colonies at 100% leachate concentration. In all experimental units, the increasing addition of leachate influenced fungal growth. The fungus L.B.1 - 1 showed the best levels of toxicity at 10 and 25% concentrations. And the fungus L.B.2 - 1.D showed reduced toxicity in the experimental units. The results indicate that the fungi L.B.1 - 1 and L.B.2 - 1.D can be promising for reducing the toxicity of landfill leachate.